B. F. Skinner e o uso do controle aversivo: um estudo histórico-conceitual - MARTINS, Tatiana Evandro Monteiro (Universidade Federal do Pará, 2014)
B.F. Skinner (1904-1990) is frequently cited as having a contrary position on the use of aversive control. However, in certain passages Skinner presents a more flexible opinion about the use of this type of behavioral control. The purpose of the present study was identifying and analyzing the passages where Skinner prescribes or warns about such use. A historical-conceptual study was conducted involving eight Skinner works (Skinner 1938/1991, 1948/1975, 1953/1989, 1968/1972, 1969/1980, 1971, 1974/2006, 1989), analyzed according to the following categories: 1) the definition of aversive control and concepts involved; 2) the positive aspects of aversive control and prescribing; and 3) the negative aspects of aversive control and prohibitions. It wasn’t possible to find a specific definition of aversive control and it was observed that at certain moments Skinner justifies the use of aversive control, but does not prescribe it in general.